Accuracy of Endoscopic Ultrasound (EUS) for Staging Ampullary Tumors - Azar, Riad R. (2011)
EUS is frequently used in the evaluation of ampullary tumors. With the advent of endoscopic ampullectomy that offers diagnostic and therapeutic potential for ampullary adenoma and early cancer, accurate staging is critical